2020
DOI: 10.1007/s11606-019-05621-3
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of Physician Experience, Specialty Training, and Self-referral on Inappropriate Diagnostic Imaging

Abstract: BACKGROUND: Although previous research has demonstrated high rates of inappropriate diagnostic imaging, the potential influence of several physician-level characteristics is not well established. OBJECTIVE: To examine the influence of three types of physician characteristics on inappropriate imaging: experience, specialty training, and self-referral. DESIGN: A retrospective analysis of over 70,000 MRI claims submitted for commercially insured individuals. Physician characteristics were identified through a com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(7 citation statements)
references
References 40 publications
0
7
0
Order By: Relevance
“…The final theme addressed by our focus groups examined the value of senior physicians. Whereas some studies suggest that outcomes in elderly patients treated by younger physicians are worse and result in a higher mortality, other research notes the positive impact of seniority on clinical efficiency, resource use, patient outcomes, and disposition in EDs 10,33,35–37 . In a commentary examining the accuracy of age‐based competency screening programs, Armstrong noted that such programs “fail to recognize the value of the accumulated wisdom and experience of older physicians.” 14 …”
Section: Discussionmentioning
confidence: 99%
“…The final theme addressed by our focus groups examined the value of senior physicians. Whereas some studies suggest that outcomes in elderly patients treated by younger physicians are worse and result in a higher mortality, other research notes the positive impact of seniority on clinical efficiency, resource use, patient outcomes, and disposition in EDs 10,33,35–37 . In a commentary examining the accuracy of age‐based competency screening programs, Armstrong noted that such programs “fail to recognize the value of the accumulated wisdom and experience of older physicians.” 14 …”
Section: Discussionmentioning
confidence: 99%
“…Patient‐level characteristics included age, gender, type of health plan (i.e., health maintenance organization/point of service; preferred provider organization, indemnity), type of clinical condition (i.e., lower back, knee, shoulder), and the median income for residential zip code (proxy for a patient's financial resources for covering deductibles and copays). We also accounted for physician experience (i.e., number of years since graduation from medical school), as this is nontime invariant and has been linked to physicians’ judgments about the appropriate use of clinical services (Young et al., 2020). In addition, we accounted for whether the physician was employed at a practice site that was owned by a hospital system.…”
Section: Empirical Specificationsmentioning
confidence: 99%
“…To conduct the investigation, we focused on referrals for inappropriate diagnostic imaging by primary care physicians (PCPs). Previous research has shown that rates of inappropriate imaging vary substantially among physician organizations and among individual physicians within the same community (Young et al., 2020). We examined whether physicians who migrated to new work environments changed their referral behavior for diagnostic imaging in a manner that conformed to the referral behavior in their new work environment.…”
Section: Introductionmentioning
confidence: 99%
“… 13 Unfortunately, there have been very few published studies of referral management among commercially insured populations and none on referral management from employer-sponsored health centers. 14 16 …”
Section: Introductionmentioning
confidence: 99%